2019
DOI: 10.18176/jiaci.0364
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Exacerbations in the Pediatric Emergency Department at a Tertiary Hospital: Association With Environmental Factors

Abstract: Introduction: Children with asthma experience recurrent respiratory symptoms and exacerbations due to multiple environmental factors. The aim of this study was to describe the prevalence and triggers of asthma exacerbations and their management in a cohort of pediatric patients attended in an emergency department (ED). Methods: We performed an observational, retrospective, single-center study in the pediatric ED of Hospital Universitario La Paz, Madrid, Spain in 2015. Children with asthma exacerbations attendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…Many studies have demonstrated so far a clear association between short-term exposure to outdoor air pollutants and different asthma outcomes including asthma control [ 87 ], lung function [ 92 ], consumption of asthma medications [ 93 , 94 ], outpatient visits [ 95 , 96 ], asthma exacerbations [ 97 , 98 ], emergency room visits [ 99 ], hospitalizations [ 100 , 101 ], length of stay in the hospital [ 102 ] and deaths [ 2 ]. Several air pollutants have been implicated in the loss of asthma control.…”
Section: Outdoor Air Pollutionmentioning
confidence: 99%
“…Many studies have demonstrated so far a clear association between short-term exposure to outdoor air pollutants and different asthma outcomes including asthma control [ 87 ], lung function [ 92 ], consumption of asthma medications [ 93 , 94 ], outpatient visits [ 95 , 96 ], asthma exacerbations [ 97 , 98 ], emergency room visits [ 99 ], hospitalizations [ 100 , 101 ], length of stay in the hospital [ 102 ] and deaths [ 2 ]. Several air pollutants have been implicated in the loss of asthma control.…”
Section: Outdoor Air Pollutionmentioning
confidence: 99%
“…However, there was insufficient evidence to draw a similar conclusion regarding adult asthma [65]. Many studies have described correlations between short-term exposure to outdoor air pollutants and various aspects of asthma, including symptom control [66], lung function [67], medication dose [68,69], outpatient visits [70,71], asthma exacerbations [72,73], emergency room visits [74], hospitalizations [75,76], length of hospital stay [77], and mortality rate [78] (Figure 1). COPD is a disease characterized by exhaustion that frequently affects smokers and involves progressive respiratory symptoms, such as dyspnea and cough with sputum.…”
Section: The Effects Of Air Pollutants On Asthma and Copd Upper Airway Diseasementioning
confidence: 99%
“…Asthma exacerbation (AE), the temporary worsening of asthma symptoms, is multifactorial in etiology. Numerous studies have reported environmental factors for AE and such contributing factors include infections (e.g., a recent study in children reported that rhinovirus (RV) species were most frequently detected, followed by respiratory syncytial virus (RSV), influenza virus, human parainfluenza viruses, and human metapneumovirus) [2], meteorological factors (e.g., temperature, humidity, wind speed, and thunderstorms), and exposure to allergens (e.g., pollen, Asian dust) or pollutants (e.g., sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), particulate matters (PMs), carbon monoxide (CO), and ozone (O 3 )) [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Therefore, environmental factors are very important causes of AEs.…”
Section: Introductionmentioning
confidence: 99%